2020
DOI: 10.5334/gh.530
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Control Post Coronary Artery Bypass Graft: One Year Follow-Up of a Middle-Eastern Cohort

Abstract: Background: Data on patient characteristics and provider practices in the management of lipids per the new guidelines in specific secondary prevention patients in the Middle East is limited. Objective: To explore patient characteristics and lipid management practices according to the new cholesterol guidelines in secondary prevention patients, up to one year following discharge for coronary artery bypass graft surgery (CABG). Methods: A retrospective chart review of patients discharged post CABG between Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Our data provide important support to the relatively few real-world studies that have investigated whether patients undergoing CABG surgery attain lipid targets. 10 11 Similar to our study, a recent study from Israel found that only 44% of CABG surgery patients attained LDL-C levels <1.8 mmol/L (70 mg/dL) at follow-up. 10 In that study, a lack of attainment of lipid targets was independently associated with decreased survival; however, we did not find a significant association between the attainment of LDL-C targets and all-cause mortality in our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our data provide important support to the relatively few real-world studies that have investigated whether patients undergoing CABG surgery attain lipid targets. 10 11 Similar to our study, a recent study from Israel found that only 44% of CABG surgery patients attained LDL-C levels <1.8 mmol/L (70 mg/dL) at follow-up. 10 In that study, a lack of attainment of lipid targets was independently associated with decreased survival; however, we did not find a significant association between the attainment of LDL-C targets and all-cause mortality in our study.…”
Section: Discussionsupporting
confidence: 89%
“… 10 Another study from the Middle East found that only 29% and 59.3% of CABG surgery patients attained LDL-C targets of <1.4 mmol/L (54 mg/dL) and <1.8 mmol/L (70 mg/dL) respectively. 11 Data from large registry studies in primary and secondary prevention cohorts in Europe have also shown that the ESC/EAS 2016 and 2019 guideline targets were attained in fewer than half and one-fifth of patients prescribed statin therapy, respectively. 19 Thus, despite the relative paucity of publications, it is evident that there remains an important gap in secondary prevention of CVD for CABG surgery patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, under-implementation of the guideline recommended LDL-C target in the CABG population is common. Results from 1-year follow-up of a Middle-Eastern cohort showed that 59.3% and 29% of CABG patients attained LDL-C targets of <1.8 mmol/L and 1.4 mmol/L, respectively (31). A most recent study from Australia with a median follow-up of 483 days reported that the attainment of LDL-C target <1.8 mmol/L was 47.7%and that of Frontiers in Cardiovascular Medicine 06 frontiersin.org <1.4 mmol/L was 24.4% (32).…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, a significant proportion of patients who have undergone CABG currently remain undertreated and have not attained guideline‐recommended levels of LDL‐C reduction. 14 , 15 , 16 It is important to investigate the lipid status of patients with MVD after CABG for clinicians to rationally adopt aggressive strategies to improve the prognosis of these patient populations. To date, there is a dearth of data on lipid status, lipid goal attainment after CABG, and the relationship between the attainment of lipid goals and long‐term outcomes.…”
mentioning
confidence: 99%